Method for preparing polylactic acid bone nail through oriented crystallization induction of bone-like structure hydroxyapatite whisker and prepared polylactic acid bone nail

Through hydroxyapatite whisker orientation crystallization induction, high-strength, high-activity, pH adaptive polylactic acid bone nails were prepared, which solved the problem of mismatch between the degradation rate of existing bone nails and the acidity of new bone growth rate and the degradation product, and achieved improvement in mechanical properties and adaptability to the degradation environment.

CN119701100APending Publication Date: 2025-03-28NINGBO BAOTING BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411925487.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The degradation rate of existing polylactic acid bone nails does not match the growth rate of new bone, and the degradation product is acidic, which is prone to inflammation.

Method used

High-strength, high-activity, pH-adaptive polylactic acid bone nails were prepared through hydroxyapatite whisker orientation crystallization induction. The method includes dispersing hydroxyapatite nanowhiskers in a polylactic acid melt, performing melt electrospinning, and subsequently introducing MgO nanocapsules through electrostatic spray, and performing hot pressing to form a polylactic acid composite material, and finally preparing bone nails by processing and sterilization.

Benefits of technology

The mechanical properties of polylactic acid bone nails are significantly improved, their absorption matches the osteogenesis rate, and the degradation environment is adaptively adjusted by pH, reducing the production of acid products and enhancing their application potential in bone repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701100A_ABST
    Figure CN119701100A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a polylactic acid bone nail through oriented crystallization induction of bone-like structure hydroxyapatite whiskers and the prepared polylactic acid bone nail, and belongs to the technical field of biological materials. The method for preparing the polylactic acid bone nail comprises the following steps: dispersing hydroxyapatite nanowhiskers in a polylactic acid melt, and carrying out melt electrostatic spinning to obtain a polylactic acid fiber membrane; the preparation method comprises the following steps: by taking an antibacterial agent as a modifier, carrying out modification treatment on a polylactic acid fiber membrane to obtain an antibacterial agent modified polylactic acid membrane, and introducing MgO nanocapsules on the antibacterial agent modified polylactic acid membrane through electrostatic spraying to obtain a MgO modified polylactic acid membrane; carrying out hot press molding treatment on the MgO modified polylactic acid film to prepare a polylactic acid composite material; and processing and sterilizing to obtain the polylactic acid bone nail. The polylactic acid bone nail which is high in strength, high in activity, self-adaptive in pH and matched in absorption rate and osteogenesis rate is obtained through oriented crystallization induction of the hydroxyapatite whiskers, and the method is simple, easy to implement and high in efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomaterials, and more specifically to a method for preparing a polylactic acid bone screw by inducing oriented crystallization of hydroxyapatite whiskers with a bone-like structure and the prepared polylactic acid bone screw. Background Art

[0002] In bone tissue engineering, since metal materials require a second surgery to remove them, while biodegradable materials can be absorbed by the human body, avoiding a second surgery and being more beneficial to postoperative recovery, biodegradable materials have gradually replaced some metal materials and played a key role in bone repair implantable devices.

[0003] Polylactic acid (PLA) is a synthetic, degradable polymer material with excellent biomechanical properties and good biodegradability. It has developed rapidly in clinical medicine, especially bone repair engineering, in the past two decades and has been widely used. In bone tissue engineering, polylactic acid is usually used as a scaffold combined with other additives or surface modified. "Materials Science and Engineer: C" (2019, Issue 110, Page 110595) reported the use of fused deposition modeling to generate polylactic acid scaffolds through 3D printing, and reinforced with graphene oxide (GO) to obtain a composite material with improved mechanical strength. "Journal of Applied Polymer Science." (2023, Issue 141, Page 55041) reported the modification of polylactic acid / starch (ST) blends by silane coupling agents to enhance the interfacial adhesion between ST and polylactic acid and improve the tensile strength of ST-filled polylactic acid materials. However, the polylactic acid scaffolds currently used in bone repair cannot match the growth rate of new bone due to their slow degradation rate, and the degradation products of polylactic acid are acidic and easily cause inflammation. Summary of the invention

[0004] In view of the above problems, the present invention provides a method for preparing a polylactic acid bone nail by inducing the oriented crystallization of hydroxyapatite whiskers with a bone-like structure and the prepared polylactic acid bone nail. The present invention obtains a polylactic acid bone nail with high strength, high activity, pH self-adaptation and absorption and bone formation rate matching by inducing the oriented crystallization of hydroxyapatite whiskers. The method is simple, easy to implement and highly efficient.

[0005] The first object of the present invention is to provide a method for preparing a polylactic acid bone nail by inducing oriented crystallization of hydroxyapatite whiskers with a bone-like structure, comprising the following steps:

[0006] The hydroxyapatite nano whiskers are dispersed in a polylactic acid melt and melt electrospinning is performed to obtain a polylactic acid fiber membrane.

[0007] The polylactic acid fiber membrane is modified with an antibacterial agent as a modifier to obtain an antibacterial agent modified polylactic acid membrane, and MgO nanocapsules are introduced into the antibacterial agent modified polylactic acid membrane by electrostatic spraying to obtain a MgO modified polylactic acid membrane.

[0008] The MgO-modified polylactic acid film is subjected to a hot-pressing molding process, and the MgO-modified polylactic acid film is subjected to hot-pressing to induce interface crystallization, so as to prepare a polylactic acid composite material.

[0009] The polylactic acid bone nail is prepared by processing and sterilizing the polylactic acid composite material.

[0010] In a preferred embodiment of the present invention, the addition amount of hydroxyapatite nano whiskers is 0.1% to 2.5% by mass of the polylactic acid melt. For example, the addition amount of hydroxyapatite nano whiskers is 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, etc., based on the mass of the polylactic acid melt, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are equally applicable.

[0011] In a preferred embodiment of the present invention, the melt electrospinning processing temperature is 100°C to 300°C, for example, the melt electrospinning processing temperature is 100°C, 150°C, 200°C, 250°C, 300°C, etc.

[0012] The receiving distance is 4.5cm to 20cm. For example, the receiving distance is 4.5cm, 6cm, 7.5cm, 9cm, 10.5cm, 12cm, 13.5cm, 15cm, 16.5cm, 18cm, 20cm, etc.

[0013] The voltage is 10 kV to 50 kV, for example, the voltage is 10 kV, 20 kV, 30 kV, 40 kV, 50 kV, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0014] In a preferred embodiment of the present invention, the added amount of the antibacterial agent is 0.002% to 25% of the mass of the polylactic acid fiber membrane. For example, the added amount of the antibacterial agent is 0.002%, 0.01%, 0.1%, 1%, 3%, 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 21%, 23%, 25%, etc., of the mass of the polylactic acid fiber membrane, but is not limited to the listed values, and other values ​​not listed within the above numerical range are equally applicable.

[0015] In a preferred embodiment of the present invention, the antibacterial agent is peracetic acid, imidazoles, quaternary ammonium salts, chitosan or polydopamine.

[0016] The modification treatment method is at least one of dipping, coating, blending, lamination, electrostatic spinning and electrostatic spraying.

[0017] In a preferred embodiment of the present invention, the preparation method of MgO nanocapsules is: adding magnesium oxide nanoparticles into water, adding vesicle components and hydrophilic components to obtain MgO nanocapsules.

[0018] In a preferred embodiment of the present invention, the amount of magnesium oxide nanoparticles added is 0.025% to 3% of the mass of the antibacterial agent modified polylactic acid fiber membrane. For example, the amount of magnesium oxide nanoparticles added is 0.025%, 0.1%, 0.5%, 1%, 1.5%, 3%, etc., of the mass of the antibacterial agent modified polylactic acid fiber membrane, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are equally applicable.

[0019] In a preferred embodiment of the present invention, in the electrostatic spray method, the receiving distance is 10 cm to 30 cm, for example, the receiving distance is 10 cm, 12 cm, 14 cm, 16 cm, 18 cm, 20 cm, 22 cm, 24 cm, 26 cm, 28 cm, 30 cm, etc.

[0020] The voltage is 10 kV to 35 kV, for example, the voltage is 10 kV, 15 kV, 20 kV, 25 kV, 30 kV, 35 kV, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0021] In a preferred embodiment of the present invention, the pressure of hot pressing is 5 MPa to 10 MPa, for example,

[0022] The pressure of hot pressing molding is 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa, etc.

[0023] The temperature is 60°C to 120°C, for example, the temperature is 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc.

[0024] The molding time is 10s to 24h, for example, the molding time is 10s, 1h, 2h, 4h, 8h, 12h, 16h, 20h, 24h, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0025] The second object of the present invention is to provide the polylactic acid bone screw prepared by the above method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention obtains a polylactic acid bone nail with high strength, high activity, pH self-adaptation and absorption matching with the bone formation rate by preparing hydroxyapatite (HA) whisker oriented crystallization induction. The method is simple, easy to implement and efficient. First, melt shearing assisted dispersion is used to peel and disperse the bone-like structure HA nano whiskers in the polylactic acid matrix, and melt spinning is performed to obtain a highly oriented polylactic acid fiber membrane; then, MgO nanocapsules are compounded with the fiber membrane introduced with an antibacterial agent by electrostatic spraying, and the polylactic acid composite is obtained by pressing and heat treatment to induce interfacial crystallization, thereby improving the overall crystallinity and mechanical strength; processing and sterilization are used to obtain the final polylactic acid bone nail with high strength, high activity, pH self-adaptation and absorption matching with the bone formation rate. In summary, the method can greatly improve the mechanical properties of polylactic acid materials in medical environments, and polylactic acid bone nails with different degradation rates can be prepared by regulating the ratio of bone-like HA whiskers and nanocapsules. At the same time, the nanocapsules can respond to pH to release MgO to achieve environmental adaptive pH regulation, which can match the complex environment in the body in bone repair, and has broad medical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A technical roadmap provided for the present invention.

[0029] Figure 2 This is a SEM image of the hydroxyapatite nanowhiskers used in the present invention.

[0030] Figure 3 This is the polylactic acid fiber induced by hydroxyapatite nano whiskers in oriented crystallization in Example 1. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] A method for preparing a polylactic acid bone nail, such as Figure 1 As shown, the following steps are included:

[0033] The hydroxyapatite nano whiskers are dispersed in a polylactic acid melt and melt electrospinning is performed to obtain a polylactic acid fiber membrane.

[0034] The polylactic acid fiber membrane is modified with an antibacterial agent as a modifier to obtain an antibacterial agent modified polylactic acid membrane, and MgO nanocapsules are introduced into the antibacterial agent modified polylactic acid membrane by electrostatic spraying to obtain a MgO modified polylactic acid membrane.

[0035] The MgO-modified polylactic acid film is subjected to a hot-pressing molding process, and the MgO-modified polylactic acid film is subjected to hot-pressing to induce interface crystallization, so as to prepare a polylactic acid composite material.

[0036] The polylactic acid bone nail is prepared by processing and sterilizing the polylactic acid composite material.

[0037] The polylactic acid bone nail prepared by the present invention has high strength, high activity, and pH adaptability, and its absorption is matched with the bone formation rate, which significantly improves the mechanical properties of the polylactic acid material in a medical environment, and polylactic acid bone nails with different degradation rates can be prepared by regulating the ratio of bone-like HA whiskers and nanocapsules. At the same time, the nanocapsules can release MgO in response to pH to achieve environmental adaptive pH regulation, which can match the complex environment in the body during bone repair, and has broad medical application prospects.

[0038] In a preferred embodiment of the present invention, the amount of hydroxyapatite nano whiskers added is 0.1% to 2.5% of the mass of the polylactic acid fiber film. During dispersion, at least one of a twin-screw extruder, a melt mixer, and an internal mixer is used for melt shearing assisted dispersion. The aspect ratio of the hydroxyapatite nano whiskers used in the present invention is 3.2-7.5, and the diameter is 15.5nm to 34.8nm. During the preparation process, the amount of hydroxyapatite nano whiskers added needs to be weighed according to the above-mentioned mass percentage. If it exceeds the above parameter range, the amount of hydroxyapatite nano whiskers added is too low, for example, less than 1%, which will lead to a significant decrease in mechanical properties such as tensile strength and bending strength; when the amount of hydroxyapatite nano whiskers added is relatively high, it will lead to a decrease in the degradation performance of the bone screw.

[0039] In a preferred embodiment of the present invention, the melt electrospinning processing temperature is 100° C. to 300° C., the receiving distance is 4.5 to 20 cm, and the voltage is 10 to 50 kV.

[0040] In a preferred embodiment of the present invention, the added amount of the antibacterial agent is 0.002% to 25% of the mass of the polylactic acid fiber membrane.

[0041] In a preferred embodiment of the present invention, the antibacterial agent is peracetic acid, imidazoles, quaternary ammonium salts, chitosan, polydopamine. When the antibacterial agent is introduced into the present invention, the method used is at least one of dipping, coating, blending, lamination, electrostatic spinning, and electrostatic spraying.

[0042] In a preferred embodiment of the present invention, the preparation method of MgO nanocapsules is: adding magnesium oxide nanoparticles to water, adding vesicle components and hydrophilic components to obtain MgO nanocapsules. The vesicle components in the MgO nanocapsules used in the present invention are at least one of sodium alginate, chitosan, polyaniline, polysaccharide and liposomal doxorubicin, and the diameter of the MgO nanoparticles is 10nm to 100nm. The hydrophilic component is hexadecane.

[0043] In a preferred embodiment of the present invention, the added amount of magnesium oxide nanoparticles is 0.025% to 3% of the mass of the antibacterial agent modified polylactic acid fiber membrane.

[0044] In a preferred embodiment of the present invention, in the electrostatic spray method, the receiving distance is 10 cm to 30 cm, and the voltage is 10 kV to 35 kV.

[0045] In a preferred embodiment of the present invention, the pressure of hot pressing is 5 MPa to 10 MPa, the temperature is 60° C. to 120° C., and the molding time is 10 s to 24 h.

[0046] In a preferred embodiment of the present invention, the processing method is at least one of laser cutting, electric spark machining, multi-axis machining and other new subtractive manufacturing processes.

[0047] In a preferred embodiment of the present invention, the sterilization method is at least one of ethylene oxide (Ethylene Oxide, EtO) sterilization and γ-irradiation sterilization.

[0048] The hydroxyapatite nano whiskers of the present invention were purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a specification of ≥97% and a product number of H811001. The SEM image of the hydroxyapatite nano whiskers is as follows: Figure 2 Chitosan has a molecular weight of 30,000 and was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of C850346. Polyaniline was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of P824522 and a specification of 98%.

[0049] Example 1

[0050] A high-strength polylactic acid bone nail and a preparation method thereof, comprising the following steps:

[0051] S1. Preparation of polylactic acid fiber membrane

[0052] 5.6 g of hydroxyapatite nano whiskers were added to 50 ml of water to obtain a hydroxyapatite nano whisker aqueous solution. The 50 ml hydroxyapatite nano whisker aqueous solution was melt-sheared and dispersed in 250 g of polylactic acid melt at 185° C. using a twin-screw extruder with a screw diameter of 40 mm. The polylactic acid fiber membrane was spun at a temperature of 100° C., a receiving distance of 10 cm, and a voltage of 20 V. Figure 3 shown.

[0053] S2. Preparation of polylactic acid composite material

[0054] 0.5 g of chitosan was added into 500 ml of water to obtain a chitosan antibacterial agent aqueous solution, and 100 g of polylactic acid fiber membrane was immersed in the 500 ml chitosan antibacterial agent aqueous solution for 12 hours to obtain a modified polylactic acid membrane.

[0055] Weigh 1.32 g of magnesium oxide nanoparticles and add them to 25 ml of water to obtain a 5% aqueous solution of magnesium oxide nanoparticles. Disperse 25 ml of the 5% aqueous solution of magnesium oxide nanoparticles into 200 ml of a 0.03% aqueous chitosan solution and 200 ml of hexadecane. Stir at 25 °C for 12 h and centrifuge to obtain a magnesium oxide nanocapsule solution.

[0056] The prepared MgO nanocapsule solution was compounded with 100 g of modified polylactic acid film by electrostatic spraying at a receiving distance of 10 cm and a voltage of 35 kV, and then hot-pressed at 120° C. and a reaction pressure of 5 MPa for 24 h to induce interface crystallization, thereby obtaining a polylactic acid composite material.

[0057] S3, preparation of high-strength polylactic acid bone nails: the polylactic acid composite material was laser cut at a power of 500 W and a cutting speed of 5 mm / s, and then heated to 50°C, with a humidity of 40%, and an ethylene oxide concentration of 700 g / cm 3 The high-strength polylactic acid bone screw was obtained by sterilizing under the conditions for 24 hours.

[0058] Example 2

[0059] A high-strength polylactic acid bone nail and a preparation method thereof, comprising the following steps:

[0060] S1. Preparation of polylactic acid fiber membrane

[0061] 0.251 g of hydroxyapatite nanowhisker was added into 50 ml of water to obtain an aqueous solution of hydroxyapatite nanowhisker. The 50 ml aqueous solution of hydroxyapatite nanowhisker was melt-shear dispersed in 250 g of polylactic acid melt in a melt mixer. The polylactic acid fiber membrane was spun at a temperature of 300°C, a receiving distance of 4.5 cm and a voltage of 4 kV.

[0062] S2. Preparation of polylactic acid composite material

[0063] 55.6 g of peracetic acid was added into 500 ml of water to obtain a peracetic acid antibacterial agent solution, and 500 ml of the peracetic acid antibacterial agent solution was coated on 100 g of the polylactic acid fiber film to obtain a modified polylactic acid film.

[0064] Weigh 0.25g of magnesium oxide nanoparticles and add it to 25ml of water to obtain an aqueous solution of magnesium oxide nanoparticles with a mass concentration of 1%. Disperse 25ml of the aqueous solution of magnesium oxide nanoparticles with a mass concentration of 1% into 200ml of a polyaniline aqueous solution with a mass concentration of 15% and 200ml of hexadecane. Stir and centrifuge at 25°C for 12h to obtain a magnesium oxide nanocapsule solution with a mass fraction of 3.2%.

[0065] The prepared magnesium oxide nanocapsule solution was compounded with 100 g of modified polylactic acid film by electrostatic spraying at a receiving distance of 30 cm and a voltage of 10 kV, and then hot-pressed at 60° C. and a reaction pressure of 10 MPa for 10 s to induce interface crystallization to obtain a polylactic acid composite material.

[0066] S3. Preparation of high-strength polylactic acid bone screws: The polylactic acid composite material is subjected to electrospark machining at a power of 13 KVA, a working distance of 350 mm, and a processing speed of 40 mm / min, and then subjected to γ-irradiation sterilization at a γ-ray dose of 20 kGy to obtain a high-strength polylactic acid bone screw.

[0067] Example 3

[0068] A high-strength polylactic acid bone nail and a preparation method thereof, comprising the following steps:

[0069] S1. Preparation of polylactic acid fiber membrane

[0070] 2.63 g of hydroxyapatite nanowhiskers were added into 50 ml of water to obtain an aqueous solution of hydroxyapatite nanowhiskers. The 50 ml aqueous solution of hydroxyapatite nanowhiskers was melt-shear dispersed in 250 g of polylactic acid melt in an internal mixer. The polylactic acid fiber membrane was spun at a temperature of 200°C, a receiving distance of 7.5 cm, and a voltage of 30 kV.

[0071] S2. Preparation of polylactic acid composite material

[0072] Prepare 1 L of 2 mg / mL dopamine solution, slowly add 1 M NaOH to adjust the pH to 9.0, pour into a culture dish and stir for 1 day to obtain a polydopamine solution.

[0073] 10 g of polydopamine solution and 100 g of polylactic acid film were melt-blended at 300° C. for 1 day and then cast into a film again to introduce the polydopamine antibacterial agent into the polylactic acid fiber film to obtain a modified polylactic acid film.

[0074] Weigh 2.78 g of magnesium oxide nanoparticles and add them to 25 ml of water to obtain a 10% aqueous solution of magnesium oxide nanoparticles. Disperse 25 ml of the 10% aqueous solution of magnesium oxide nanoparticles into 200 ml of a 0.02% aqueous sodium alginate solution and 200 ml of hexadecane. Stir at 25°C for 12 hours and centrifuge to obtain a magnesium oxide nanocapsule solution.

[0075] At a receiving distance of 15 cm and a voltage of 15 kV, the prepared MgO nanocapsule solution was compounded with 100 g of modified polylactic acid film by electrostatic spraying, and hot pressing was performed at 100° C. and a reaction pressure of 7 MPa for 4 h to induce interface crystallization, thereby obtaining a polylactic acid composite material.

[0076] S3, preparation of high-strength polylactic acid bone nails: the polylactic acid composite material was processed by multi-axis at a cutting speed of 50 m / min and a feed rate of 0.3 mm / rev, and then at a temperature of 50°C, a humidity of 40%, and an ethylene oxide concentration of 700 g / cm 3 The high-strength polylactic acid bone screw was obtained by sterilizing under the conditions for 24 hours.

[0077] Example 4

[0078] A high-strength polylactic acid bone nail and a preparation method thereof, comprising the following steps:

[0079] S1. Preparation of polylactic acid fiber membrane

[0080] 0.05 g of hydroxyapatite nanowhisker was added into 50 ml of water to obtain an aqueous solution of hydroxyapatite nanowhisker. The 50 ml aqueous solution of hydroxyapatite nanowhisker was melt-shear dispersed in 250 g of polylactic acid melt in a twin-screw extruder. The polylactic acid fiber membrane was spun at a temperature of 150°C, a receiving distance of 6 cm, and a voltage of 40 kV.

[0081] S2. Preparation of polylactic acid composite material

[0082] 52.63 g of benzalkonium chloride was added to 1 L of water to obtain a quaternary ammonium salt antibacterial agent aqueous solution, and 1 L of the quaternary ammonium salt antibacterial agent aqueous solution was introduced into 100 g of polylactic acid fiber membrane by hot pressing at 100° C. for 20 min to obtain a modified polylactic acid membrane.

[0083] 25 ml of 5% magnesium oxide nanoparticle aqueous solution was dispersed into 200 ml of 15% polyaniline aqueous solution and 200 ml of hexadecane, and the mixture was stirred at 25° C. for 12 h and centrifuged to obtain a magnesium oxide nanocapsule solution with a mass fraction of 3.2%.

[0084] At a receiving distance of 20 cm and a voltage of 20 kV, the prepared MgO nanocapsule solution was compounded with 100 g of modified polylactic acid film by electrostatic spraying, and hot pressed at 80° C. and a reaction pressure of 9 MPa for 5 min to induce interface crystallization, thereby obtaining a polylactic acid composite material.

[0085] S3. Preparation of high-strength polylactic acid bone screws: The polylactic acid composite material is laser processed at a power of 500 W and a cutting speed of 5 mm / s, and then sterilized by γ-irradiation to obtain high-strength polylactic acid bone screws.

[0086] Example 5

[0087] A high-strength polylactic acid bone nail and a preparation method thereof, comprising the following steps:

[0088] S1. Preparation of polylactic acid fiber membrane

[0089] 2.63 g of hydroxyapatite nanowhiskers were added into 50 ml of water to obtain a hydroxyapatite nanowhiskers aqueous solution. 50 ml of hydroxyapatite nanowhiskers were melt-shear dispersed in 250 g of polylactic acid melt in a melt mixer. The polylactic acid fiber membrane was spun at a temperature of 250° C., a receiving distance of 5 cm, and a voltage of 25 kV.

[0090] S2. Preparation of polylactic acid composite material

[0091] 17.65 g of clotrimazole was added to 118 ml of water to obtain an imidazole antibacterial agent aqueous solution. At a receiving distance of 8 cm and a voltage of 20 kV, the configured imidazole antibacterial agent aqueous solution with a mass concentration of 15% was introduced into 100 g of polylactic acid fiber membrane using electrospinning to obtain a modified polylactic acid membrane.

[0092] Weigh 0.025g of magnesium oxide nanoparticles and add it to 25ml of water to obtain an aqueous solution of magnesium oxide nanoparticles with a mass concentration of 0.1%. Disperse 25ml of the aqueous solution of magnesium oxide nanoparticles with a mass concentration of 0.1% into 200ml of a polyaniline aqueous solution with a mass concentration of 15% and 200ml of hexadecane, stir at 25°C for 12h and centrifuge to obtain a magnesium oxide nanocapsule solution.

[0093] At a receiving distance of 25 cm and a voltage of 25 kV, the prepared MgO nanocapsule solution was compounded with 100 g of modified polylactic acid film by electrostatic spraying, and hot pressed at 90° C. and a reaction pressure of 8 MPa for 20 min to induce interface crystallization, thereby obtaining a polylactic acid composite material.

[0094] S3. Preparation of high-strength polylactic acid bone nails: The polylactic acid composite material was electrospark machined at a γ-ray dose of 20 Gy at a temperature of 50 ° C, a humidity of 40%, and an ethylene oxide concentration of 700 g / cm 3The mixture was sterilized under the conditions for 24 hours to obtain a high-strength polylactic acid bone screw.

[0095] Example 6

[0096] A high-strength polylactic acid bone nail and a preparation method thereof, comprising the following steps:

[0097] S1. Preparation of polylactic acid fiber membrane

[0098] 1.25 g of hydroxyapatite nanowhiskers were added into 50 ml of water to obtain a hydroxyapatite nanowhiskers aqueous solution. 50 ml of hydroxyapatite nanowhiskers were melt-shear dispersed in 250 g of polylactic acid melt in a melt mixer. The polylactic acid fiber membrane was spun at a temperature of 200°C, a receiving distance of 5 cm, and a voltage of 10 kV.

[0099] S2. Preparation of polylactic acid composite material

[0100] 37.5 g of clotrimazole was added to 150 ml of water to obtain an imidazole antibacterial agent aqueous solution. The prepared imidazole antibacterial agent aqueous solution was introduced into 100 g of polylactic acid fiber membrane by electrospinning at a receiving distance of 8 cm and a voltage of 20 kV to obtain a modified polylactic acid membrane.

[0101] Weigh 3 g of magnesium oxide nanoparticles and add them to 25 ml of water to obtain an aqueous solution of magnesium oxide nanoparticles with a mass concentration of 12%. Disperse 25 ml of the aqueous solution of magnesium oxide nanoparticles with a mass concentration of 12% into 200 ml of a polyaniline aqueous solution with a mass concentration of 15% and 200 ml of hexadecane, stir at 25°C for 12 hours and centrifuge to obtain a magnesium oxide nanocapsule solution.

[0102] At a receiving distance of 25 cm and a voltage of 25 kV, the prepared MgO nanocapsule solution was compounded with 100 g of modified polylactic acid film by electrostatic spraying, and hot pressed at 70° C. and a reaction pressure of 8 MPa for 1 h to induce interface crystallization, thereby obtaining a polylactic acid composite material.

[0103] S3. Preparation of high-strength polylactic acid bone nails: The polylactic acid composite material was electrospark machined at a γ-ray dose of 20 Gy, at a temperature of 50 ° C, a humidity of 40%, and an ethylene oxide concentration of 700 g / cm 3 The mixture was sterilized under the conditions for 24 hours to obtain a high-strength polylactic acid bone screw.

[0104] Comparative Example 1

[0105] S1. Spin 250 g of polylactic acid melt at a temperature of 100° C., a receiving distance of 10 cm, and a voltage of 20 kV to obtain a polylactic acid fiber film.

[0106] S2. Add 0.5 g of chitosan into 500 ml of water to obtain a chitosan antibacterial agent aqueous solution, immerse 100 g of the polylactic acid fiber membrane in the 500 ml chitosan antibacterial agent aqueous solution for 12 hours to obtain a modified polylactic acid membrane.

[0107] Weigh 1.32 g of magnesium oxide nanoparticles and add them to 25 ml of water to obtain a 5% aqueous solution of magnesium oxide nanoparticles. Disperse 25 ml of the 5% aqueous solution of magnesium oxide nanoparticles into 200 ml of a 0.03% aqueous chitosan solution and 200 ml of hexadecane. Stir at 25 °C for 12 h and centrifuge to obtain a magnesium oxide nanocapsule solution.

[0108] The prepared MgO nanocapsule solution was compounded with 100 g of modified polylactic acid film by electrostatic spraying at a receiving distance of 10 cm and a voltage of 35 kV, and then hot-pressed at 120° C. and a reaction pressure of 5 MPa for 24 h to induce interface crystallization, thereby obtaining a polylactic acid composite material.

[0109] S3, after the polylactic acid composite material is laser cut at a power of 500 W and a cutting speed of 5 mm / s, the temperature is 50°C, the humidity is 40%, and the ethylene oxide concentration is 700 g / cm 3 The high-strength polylactic acid bone screw was obtained by sterilizing under the conditions for 24 hours.

[0110] Comparative Example 2

[0111] S1. Add 0.251 g of hydroxyapatite nanowhiskers into 50 ml of water to obtain a hydroxyapatite nanowhiskers aqueous solution. In a melt mixer, melt and shear disperse 50 ml of hydroxyapatite nanowhiskers with a mass concentration of 0.5% in 250 g of polylactic acid melt. Spin at a temperature of 300°C, a receiving distance of 4.5 cm, and a voltage of 45 kV to obtain a polylactic acid fiber membrane.

[0112] S2. Add 55.6 g of peracetic acid into 500 ml of water to obtain a peracetic acid antibacterial agent solution, and apply 500 ml of the peracetic acid antibacterial agent solution with a mass concentration of 10% on the above-mentioned polylactic acid fiber membrane to obtain a modified polylactic acid membrane.

[0113] S3. After electrospark machining at a power of 13KVA, a working distance of 350mm, and a machining speed of 40mm / min, γ-irradiation sterilization was performed under the condition of a γ-ray dose of 20kGy to obtain a high-strength polylactic acid bone screw.

[0114] Comparative Example 3

[0115] S1. Add 2.63 g of hydroxyapatite nanowhiskers into 50 ml of water to obtain a hydroxyapatite nanowhiskers aqueous solution. In an internal mixer, melt-shear-disperse 50 ml of hydroxyapatite nanowhiskers with a mass concentration of 5% in 250 g of polylactic acid melt. Spin at a temperature of 200°C, a receiving distance of 7.5 cm, and a voltage of 30 kV to obtain a polylactic acid fiber membrane.

[0116] S2. Prepare 1 L of 2 mg / mL dopamine solution, slowly add 1 M NaOH to adjust the pH to 9.0, pour into a culture dish and stir for 1 day to obtain a polydopamine solution.

[0117] 10 g of polydopamine solution and 100 g of polylactic acid film were melt-blended at 300° C. for 1 day and then cast into a film again to introduce the polydopamine antibacterial agent into the polylactic acid fiber film to obtain a modified polylactic acid film.

[0118] Weigh 2.78 g of magnesium oxide nanoparticles and add them to 25 ml of water to obtain a 10% aqueous solution of magnesium oxide nanoparticles. Disperse 25 ml of the 10% aqueous solution of magnesium oxide nanoparticles into 200 ml of sodium alginate and 200 ml of hexadecane, stir at 25°C for 12 h, and centrifuge to obtain a magnesium oxide nanocapsule solution.

[0119] At a receiving distance of 15 cm and a voltage of 15 kV, the prepared MgO nanocapsule solution was compounded with 100 g of the modified polylactic acid film by electrostatic spraying to obtain a polylactic acid composite material.

[0120] S3. Processing the polylactic acid composite material by multi-axis at a cutting speed of 50 m / min and a feed rate of 0.3 mm / rev, followed by ethylene oxide (EtO) sterilization to obtain a high-strength polylactic acid bone screw.

[0121] Performance Testing

[0122] Mechanical properties test: The mechanical properties of the bone screws were tested according to the ASTM F543 standard. The tensile strength, elongation at break, flexural strength, flexural modulus and torsional yield strength of the bone screws were tested using the PBSC-RP30 bone screw performance tester.

[0123] In vivo degradation behavior and in vivo pH test after degradation: Referring to the report of Fu et al. on "Mechanical and biodegradable properties of hydroxyapatite composite polylactic acid absorbable screws" [Chinese Journal of Tissue Engineering Research (2013, Vol. 17, No. 38, p. 6709)], the mechanical strength and biodegradation rate of polylactic acid bone screws in vivo were determined using the canine femoral lateral condyle fracture internal fixation model. Beagles were anesthetized intravenously with 3% pentobarbital (1.0 mL / kg), fixed in supine position, bilateral knee joints were shaved, the skin was routinely cleaned and disinfected with iodine tincture, and sterile towels were laid. An incision was made on the lateral side of the knee joint to expose the lateral femoral condyle. The lateral femoral condyle was longitudinally folded with a thin bone knife to cause a simple lateral femoral condyle fracture with a depth of about 1 cm until the medial femoral condyle bone block was loosened. A hole was drilled with an electric drill from 1 / 3 of the medial femoral condyle fracture block, and the hole was expanded with a tap. The two nails were fixed in parallel, and the fracture blocks were checked for firm fixation and good joint surface alignment. Antibiotics were given for 3 days after surgery to prevent infection, with penicillin 80×10 4 U was injected intramuscularly twice a day, and 8U of gentamicin was injected intramuscularly twice a day. No external fixation was performed, and the animals were free to move. After surgery, the animals were kept in separate cages. After the expiration of each group of animals, an overdose of sodium pentobarbital was injected and killed. The femurs of both hind limbs were removed, and the soft tissues were removed for standby testing and observation. After 48 weeks, the screws of the test animals were removed, and their molecular weight was measured using a high-performance liquid chromatograph (gel chromatography column), and the degradation rate was calculated by molecular weight. The pH value of the in vivo environment was measured using a pH meter.

[0124]

[0125] Table 1 Mechanical properties and degradation performance test results

[0126]

[0127] Table 1 compares the mechanical strength, degradation rate and pH value of the degradation environment of the polylactic acid bone screws obtained in the embodiments and comparative examples. The bone screws of Examples 1 to 5 have a tensile strength of 55 MPa to 90 MPa, an elongation at break of 5.1% to 8.2%, which is about 1.8 times that of the comparative example, a flexural strength of 111.3 MPa to 187.2 MPa, a flexural modulus of 2100 MPa to 4189 MPa, which is about 1.5 times that of the comparative example, and a torsional yield strength of 85 MPa to 180 MPa, which is about 2 times that of the comparative example, which proves that the bone screws prepared by the present invention can withstand the physiological load of the human body environment and achieve effective torsion to enter the human body. The degradation rate in the experimental beagle dogs after 48 weeks was 55.8% to 75.4%, while that in the comparative example was 78.7% to 81.3%. The degradation of the polylactic acid bone nail prepared by the present invention was significantly reduced after 48 weeks, and the pH value of the environment after degradation was 6.9 to 8.9, which was closer to the physiological environment of the human body than 6.2 to 6.5 in the comparative example, indicating that the generation of acidic products was reduced. It is proved that the preparation method of the present invention can significantly enhance the mechanical strength of polylactic acid and maintain an environment suitable for polylactic acid degradation and new bone growth, and is expected to be used in practical applications of future bone repair engineering.

[0128] This shows that the preparation method proposed in the present invention can significantly improve the mechanical properties of the polylactic acid bone nail, maintain good biological activity, and at the same time, the degradation rate and pH value after degradation can match the physiological environment of human bones. These are likely due to: (1) hydroxyapatite nanowhiskers induce oriented crystallization during the spinning process of polylactic acid, thereby achieving structural toughening and strengthening; (2) polylactic acid and hydroxyapatite nanowhiskers achieve close interface connection during the hot pressing process, which manifests as enhanced mechanical properties on a macro scale; (3) by loading MgO nanocapsules, MgO can be released in response to pH to achieve a large amount of MgO nanoparticles released at low pH to increase pH, control the degradation of polylactic acid, and can cooperate with hydroxyapatite nanowhiskers to neutralize the acidic products produced during the degradation of polylactic acid, thereby maintaining compatibility with the neutral pH environment of the human body.

[0129] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0130] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure, characterized in that: The following steps are involved: The hydroxyapatite nano whiskers are dispersed in a polylactic acid melt and melt electrospinning is performed to obtain a polylactic acid fiber membrane; Using an antimicrobial agent as a modifier, a polylactic acid fiber membrane is modified to obtain an antimicrobial agent modified polylactic acid membrane, and MgO nanocapsules are introduced into the antimicrobial agent modified polylactic acid membrane by electrostatic spraying to obtain a MgO modified polylactic acid membrane; The MgO-modified polylactic acid film was subjected to hot pressing to induce interface crystallization, thereby preparing a polylactic acid composite material; The polylactic acid bone nail is prepared by processing and sterilizing the polylactic acid composite material.

2. The method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure according to claim 1, characterized in that: The addition amount of hydroxyapatite nano whiskers is 0.1% to 2.5% of the mass of the polylactic acid melt.

3. The method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure according to claim 1, characterized in that: The melt electrospinning processing temperature is 100°C to 300°C, the receiving distance is 4.5cm to 20cm, and the voltage is 10kV to 50kV.

4. The method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure according to claim 1, characterized in that: The added amount of the antibacterial agent is 0.002% to 25% of the mass of the polylactic acid fiber membrane.

5. The method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure according to claim 1, characterized in that: The antimicrobial agent is peracetic acid, imidazoles, quaternary ammonium salts, chitosan or polydopamine; The modification treatment method is at least one of dipping, coating, blending, lamination, electrostatic spinning and electrostatic spraying.

6. The method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure according to claim 1, characterized in that: The preparation method of MgO nanocapsules is as follows: adding magnesium oxide nanoparticles into water, adding vesicle components and hydrophilic components to obtain MgO nanocapsules.

7. The method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure according to claim 6, characterized in that: The added amount of magnesium oxide nanoparticles is 0.025% to 3% of the mass of the antibacterial agent modified polylactic acid fiber membrane.

8. The method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure according to claim 1, characterized in that: In the electrostatic spray method, the receiving distance is 10 cm to 30 cm and the voltage is 10 kV to 35 kV.

9. The method for preparing polylactic acid bone nails by inducing oriented crystallization of hydroxyapatite whiskers with bone-like structure according to claim 1, characterized in that: The pressure of hot pressing is 5MPa~10MPa, the temperature is 60℃~120℃, and the molding time is 10s~24h.

10. A polylactic acid bone screw prepared by the method according to any one of claims 1 to 9.